The evolution of an idea - Hakim, Joy (Hakim, Joy. Discovering life's story, 2024)
"Can species change? Or go extinct? In the eighteenth century, most people answer no to both questions. But in the century that follows, that certainty gets challenged as some people in Europe question the common belief that all creatures are the same as they've been since life's creation. The Evolution of an Idea, the second volume of Discovering Life's Story, opens with the Swedish naturalist Carl Linnaeus, who attempts to create an organizing system for the myriad forms of life on earth. It continues into the late 1800s, when two Englishmen--Charles Darwin and Alfred Russel Wallace--each develop their own version of a startling new theory of how life-forms change over time. This evolutionary idea will alter the understanding of our place in the great web of life on earth. In this remarkable volume, author Joy Hakim continues charting the path of human discovery and shows how groundbreaking thinkers began to unlock the biological secrets of our own existence"--